Masjid in China - Yongzhong, Xia; Ali, Mohammed Farid (IIUM Press, International Islamic University Malaysia, 2017)
Through time, not only architectural development of masjids takes place. Other aspects of the masjids such as its functions in response to people’s religion and culture evolve as well. In minority Muslim countries, masjids form the focal points for religion, residence, business, education, social and politics. This work uses the descriptive phenomenological approach, interviews, and document analysis studies the religious and social functions of selected masjids of the two important large groups of Muslims in China the Hui and Uyghur. The study discovers that masjid beside worship represent the Muslim ummah in China. The direction of the Muslims can be depicted by looking at the functions that take place in their masjids. Masjids function as the ethnic identity, protector of cultural relics, historian, propagator of religious teachings, cultural and academic center, supervisor, diplomat, tourism, and so on.